The Correlation between Physical Characteristics and Motor Skills of Female Secondary School Pupils - Zoran Milošević; Jovan Vuković; Nebojša Maksimović; Radenko Matić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
Secondary school age of female pupils, specific for intensive changes of physical characteristics, in particular for variability of motor expression, is the inspiration for numerous researches as well as of "demands" of contemporary practice of physical education within schools. We have measured physical characteristics and tested motor skills of 228 female pupils of the first grades of secondary schools from Novi Sad. The evaluation of the above-mentioned characteristics and skills has been carried out using the EUROFIT Program of measuring. By applying the canonical correlation analysis we obtained the results pointing to the existence of statistically significant correlation-out of 7 potential canonical factors 3 are statistically significant, as follows: CAN1-female pupils with higher body mass and sub-skin fat are less successful at test for static strength evaluation (MIZDR), aerobic-anaerobic endurance test (MISTR), shuttle running speed (MCUNT), and static balance test (MFLAM), CAN2-female pupils with small body mass are less successful at pliability, static force and dynamic force tests, and CAN3-female pupils with exceptional body height are more successful at tests for lower extremities explosive strength measuring. Based on the insight into the obtained structure of canonical factors it can be concluded that determined correlation of body characteristics and motor skills originate up to a significant extent from feminine gender characteristics of female pupils, who, at the studied age, represent the (un)favourable biomechanical functional basis for manifesting of skills responsible for an efficient motor behaviour.